535TiPPhase II study of atezolizumab for pretreated advanced / recurrent non-small cell lung cancer with idiopathic interstitial pneumonia (TORG1936 / AMBITIOUS study). (24th November 2019) - Ikeda, S; Kato, T; Kenmotsu, H; Ogura, T; Iwasawa, S; Iwasawa, T; Kasajima, R; Miyagi, Y; Misumi, T; Yamanaka, T; Okamoto, H
Abstract: Background: Interstitial pneumonia (IP) is one of the most common and poor prognostic comorbidities in patients with non-small cell lung cancer (NSCLC) and is also a known risk factor for pneumonitis. Approximately 10% of patients have concomitant IP diagnosed at the time of cancer diagnosis. IP is associated with smoking, microsatellite instability (MSI) and higher tumour mutation burden (TMB). Atezolizumab monotherapy is an established treatment for recurrent NSCLC. PD-L1 inhibitors are reported to have a lower risk of pneumonitis than PD-1 inhibitors. This study aims to assess the safety and efficacy of atezolizumab monotherapy for pretreated advanced or recurrent NSCLC patients with idiopathic IP. Trial design: The Thoracic Oncology Research Group (TORG) 1936/AMBITIOUS study is a multicentre, single-arm, phase II trial. The key inclusion criteria are (1) histologically or cytologically proven NSCLC, (2) unresectable stage III/IV or recurrent disease, (3) prior chemotherapy, including platinum doublet chemotherapy, (4) chronic, fibrotic and idiopathic IP with a predicted vital capacity ≥ 70%, (5) age ≥ 20 years and (6) ECOG performance status 0, 1. The enrolled patients will receive atezolizumab (1200 mg) every 3 weeks until the discontinuation criteria are satisfied. The primary end point is the 1-year survival rate. We set an expected value of 40% and a threshold value of 15%. Taking statistical points (two-sided α = 0.05; 1 − β = 0.9) and ineligible patients into account, the sample size was set at 38 based on the exact binomial test. The key secondary end points are the incidence of acute exacerbation of IP within 1 year after treatment initiation, overall survival, progression-free survival, objective response rate and safety. As a translational research, we will perform analysis of TMB, somatic mutations and MSI from tumour samples. Legal entity responsible for the study: Thoracic Oncology Research Group (TORG). Funding: Chugai Pharmaceutical Co., Ltd. Disclosure: S. Ikeda: Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical; Honoraria (self): Boehringer Ingelheim; Honoraria (self): AstraZeneca; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): Ono Pharmaceutical. T. Kato: Honoraria (self), Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Astellas; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self): Boehringer Ingelheim; Honoraria (self), Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (self): Chugai Pharmaceutical; Honoraria (self), Research grant / Funding (self): Eli Lilly; Research grant / Funding (institution): Kyorin Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Kyowa Hakko Kirin; Honoraria (self), Research grant / Funding (institution): Merck Serono; Honoraria (self), Research grant / Funding (institution): Merck Sharp and Dohme; Honoraria (self): Nitto Denko; Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Pfizer; Honoraria (self): Quintiles; Research grant / Funding (institution): Regeneron; Honoraria (self): Sumitomo Dainippon Pharma; Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical; Honoraria (self): Takeda Pharmaceutical; Honoraria (self): F. Hoffmann-La Roche. H. Kenmotsu: Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical; Honoraria (self): Ono Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self): Eli Lilly ; Honoraria (self): Kyowa Hakko Kirin; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Merck Sharp and Dohme; Honoraria (self): Novartis Pharma; Honoraria (self): Daiichi-Sankyo; Honoraria (self), Research grant / Funding (institution): AstraZeneca. T. Ogura: Honoraria (self), Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self): Meiji Seika Pharma; Honoraria (self): Shionogi Pharmaceutical; Honoraria (self): Toray; Honoraria (self): AstraZeneca; Honoraria (self): Eisai; Honoraria (self): Astellas Pharma; Honoraria (self): Kyorin Pharmaceutical; Honoraria (self): Ono Pharmaceutical; Honoraria (self): Actelion Pharmaceuticals; Honoraria (self): Novartis. S. Iwasawa: Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self): AstraZeneca. T. Iwasawa: Honoraria (self): Ono pharmaceutical; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Shionogi. T. Yamanaka: Honoraria (self), Research grant / Funding (institution): Takeda Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): Eli Lilly; Honoraria (self): Pfizer; Honoraria (self): Sysmex; Honoraria (self): Huya Biosciences; Honoraria (self): Gilead Sciences. H. Okamoto: Research grant / Funding (institution): Chugai Pharmaceutical; Research grant / Funding (institution): Takeda Pharmaceutical; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Merck Sharp and Dohme; Research grant / Funding (institution): Ono Pharmaceutical; Research grant / Funding (institution): Taiho pharmaceutical; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Daiichi Sankyo. All other authors have declared no conflicts of interest.